Water management optimization model for the Razmgan agricultural district in Khorasan province, Iran - Fatemi, Seyed Mahdi (2011)
Water deficit in the dry season of semi-arid regions, (especially in low scale farms and established orchards) results in a significant decrease in agricultural productivity. This problem can be overcome by optimal operation of reservoir based on prioritization of water allocation for crops considering the sensitive growth periods. In this study, a nonlinear optimization model is employed to reduce the impact of water deficit in order to increase crop productivity and net income for farmers. The LINGO 8.0 software was used to determine the optimal amounts of both water and land for the existing cropping pattern. The LINGO model was applied to the Razmgan semi-arid area which is located 10 km south of the Shirvan city, northern Khorasan province, Iran, where irrigation needs are supplied from the river and the existing auxiliary reservoir stores the surplus water in the wet season in order to reduce the impact of water deficit in the dry season. Inefficient current water management, especially, in operation of the existing auxiliary reservoir and non optimal water allocation for crops growth periods result in a low actual yield for crops in the study area. To determine the optimal operation of the reservoir, various scenarios of the water release from the reservoir, to reduce the imposed water-stress during the crop growth stages were explored. Results of the LINGO model showed application of senario 4 results in the maximum annual net income for the farmers (USD 1,778,298), which shows 26.21% increase than the current status (USD 1,409,030). Also application of the scenario 4 overcomes the existing water deficits in the months of July, August, September, October and November, only 13% and 42.16% water deficits remain for the months of May and June, respectively, and water consumption decreases from 3,359,000 m3 in the current status to 2,999,369 m3 in the optimal status. Monthly irrigation scheduling to achieve the maximum net income was derived from the output of the model for use by the farmers. Application of the LINGO model for irrigated area subjected to the water deficit and low agricultural productivity helps to increase the current net income of the farmers.